Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1103/physreva.89.013812
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal gap solitons inPT-symmetric periodic potentials with defocusing nonlinearity

Abstract: Existence and stability of PT -symmetric gap solitons in a periodic structure with defocussing nonlocal nonlinearity are studied both theoretically and numerically. We find that, for any degree of nonlocality, gap solitons are always unstable in the presence of an imaginary potential. The instability manifests itself as a lateral drift of solitons due to an unbalanced particle flux. We also demonstrate that the perturbation growth rate is proportional to the amount of gain (loss), thus predicting the observabi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 52 publications
(74 reference statements)
1
29
0
Order By: Relevance
“…Defocusing type of nonlinearity has been considered in [120]. The existence and stability of gap solitons in media with diffusive-like nonlinear response were determined.…”
Section: Generalized Nonlinear Potentialsmentioning
confidence: 99%
“…Defocusing type of nonlinearity has been considered in [120]. The existence and stability of gap solitons in media with diffusive-like nonlinear response were determined.…”
Section: Generalized Nonlinear Potentialsmentioning
confidence: 99%
“…Based on Eqs. (11) and (12), we obtain the critical input powers of AVBs in SNNM numerically (see Fig. 1).…”
Section: Propagation Propertiesmentioning
confidence: 99%
“…Until 1993, the (2 þ1)-dimensional spatial optical solitons were observed in photorefractive media, which is an epochmaking event [3] because it is found that the saturation nonlinearity can suppress the catastrophic collapse. Nowadays, various solitons have been found in different media, such as surface solitons [4][5][6][7][8][9], PT-symmetric potential solitons [10][11][12][13][14], optical lattice solitons [15][16][17][18][19][20], and even spatiotemporal optical solitons (namely the light bullets) [21][22][23][24][25][26][27], and so on. Recently, it is found that except the saturation nonlinearity, the nonlocal nonlinearity can also suppress the catastrophic collapse in bulk media.…”
Section: Introductionmentioning
confidence: 99%
“…Bright solitons can also exist in PT-symmetric potentials with nonlocal nonlinearity [27][28][29][30][31][32]. Nonlocal fundamental and dipole defect solitons can exist in different gaps in PT-symmetric optical lattices with focusing nonlinearity [27].…”
Section: Introductionmentioning
confidence: 95%